2021
DOI: 10.3390/en14010253
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Co-Phase Power-Supply System Based on Modular Multilevel Converter for High-Speed Railway AT Traction Power-Supply System

Abstract: The existing problems of the traction power-supply system (i.e., the existence of the neutral section and the power quality problems) limit the development of railways, especially high-speed railways, which are developing rapidly worldwide. The existence of the neutral section leads to the speed loss and traction loss as well as mechanical failures, all of which threaten the fast and safe operation of the train and the system. Meanwhile, the power quality problems (e.g., the negative sequence current, the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Short-circuit faults are usually caused by strong wind, lightning, equipment failure, animals, poor insulation, etc. [11]. When the induction motor starts, its stator current increases rapidly, which increases the voltage division of the system on the impedance, resulting in a voltage sag.…”
Section: Methodsmentioning
confidence: 99%
“…Short-circuit faults are usually caused by strong wind, lightning, equipment failure, animals, poor insulation, etc. [11]. When the induction motor starts, its stator current increases rapidly, which increases the voltage division of the system on the impedance, resulting in a voltage sag.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al [22] developed the emergency power supply designed for photo-voltaic (PV) and battery accessible railway traction power supply system. The signal contained disturbance of a particular frequency during the steady-state of the system and used a Fourier transform to progress three ports of PVbattery locomotive network towards the inverter to connect the DC port.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The structure of the traction power supply system with an energy storage device is divided into vehicle-mounted storage and stationary energy storage [1]. In this paper, the general structure of the traction power supply system connected with energy storage technology is analyzed, and it is found that the structure of the stationary energy storage is more conducive to the capacity optimization of the traction transformer [22][23][24].…”
Section: Structure Of Capacity Optimization Of Traction Transformer W...mentioning
confidence: 99%